The determinants of achieving family business excellence: conservative quality perspective?. (10th November 2018) - Lin, Che-Hung
Abstract : We argue that the alignment effect and the entrenchment effect of family firms (hereafter, families) have important implications in conservative quality. We construct a conservative quality model according to four dimensions of families (such as family ownership, family management, family external supervising and family control) and the two competing effects (such as alignment effect and entrenchment effect) to assess which family dimensions are the determinants of achieving business excellence. Overall, these findings are consistent with the notion that families are excellent entities and families with external supervising (rather than family management and family control) are primarily responsible for families exhibiting fewer agency problems and more conservative quality.